Wastewater Processing of Chicken Slaughterhouses Using Combination of Trickling Filter and Rotating Biological Contactor - Handriani Handriani; Muhammad Faisal; Cut Meurah Rosnelly (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This research was conducted to explore the effectiveness of combined Trickling Filter (TF) and Rotating Biological Contactor (RBC) method in processing liquid waste from chicken slaughterhouses through local and economical media. Microorganisms were grown by inserting liquid waste into a TF tank containing gravel, used ceramics, coconut shells, and pumice. Subsequently, liquid waste flowed into a rotating biological contactor added with local microorganisms from stale rice and fermented banana stems. Waste treatment was carried out with variations in retention time of 1, 3, and 6 h. The results showed that at 6 h, the organic compound decreased significantly. The removal efficiency obtained was 87.05%, 82.11%, 90.51%, 22.57%, 79.36%, and 88.66% for Biological Oxygen Demand, Chemical Oxygen Demand, Total Suspended Solids, Total Dissolved Solids, Turbidity, and Ammonia, respectively. This high efficiency was supported by the collaboration between the activity of microorganisms attached to the TF biofilm and the use of local microorganisms in decomposing organic compounds in the rotating biological contactor. The combination of the two methods has been proven to help waste treatment process from chicken slaughterhouses in an environmentally friendly and efficient manner. Keywords: Biofilm, Chicken slaughterhouse waste, Local microorganisms, Rotating biological contactor, Trickling filter.